2018
DOI: 10.3389/fmicb.2018.02673
|View full text |Cite|
|
Sign up to set email alerts
|

Species Richness, rRNA Gene Abundance, and Seasonal Dynamics of Airborne Plant-Pathogenic Oomycetes

Abstract: Oomycetes, also named Peronosporomycetes, are one of the most important and widespread groups of plant pathogens, leading to significant losses in the global agricultural productivity. They have been studied extensively in ground water, soil, and host plants, but their atmospheric transport vector is not well characterized. In this study, the occurrence of airborne Oomycetes was investigated by Sanger sequencing and quantitative PCR of coarse and fine aerosol particle samples (57 filter pairs) collected over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…The presence of ~54% of all oomycete OTUs in both sampling events ( Figure 4B) indicates a continuous presence of both peronosporean and pythialean oomycete spores and consequently a high proportion of potentially physiologically active oomycetes, including potential pathogens within forest ecosystems. Oomycetes pose a serious threat to forest health and functioning, it is therefore crucial to better understand their diversity and distribution patterns of the total forest ecosystem, including air samples (Derevnina et al, 2016;Ajchler et al, 2017;Jung et al, 2018;Lang-Yona et al, 2018). We detected no OTUs assigned to the orders Saprolegniales, Lagenidiales or Myzocytiopsidales, even though Jauss et al (2020) found them in canopy and ground samples.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The presence of ~54% of all oomycete OTUs in both sampling events ( Figure 4B) indicates a continuous presence of both peronosporean and pythialean oomycete spores and consequently a high proportion of potentially physiologically active oomycetes, including potential pathogens within forest ecosystems. Oomycetes pose a serious threat to forest health and functioning, it is therefore crucial to better understand their diversity and distribution patterns of the total forest ecosystem, including air samples (Derevnina et al, 2016;Ajchler et al, 2017;Jung et al, 2018;Lang-Yona et al, 2018). We detected no OTUs assigned to the orders Saprolegniales, Lagenidiales or Myzocytiopsidales, even though Jauss et al (2020) found them in canopy and ground samples.…”
Section: Discussionmentioning
confidence: 74%
“…Wind dispersal is an important means for the distribution of microbial plant pathogens, and oomycetes are no exception (Fawke et al, 2015;Lang-Yona et al, 2018). Yet, comprehensive assessments of their abundances within the forest air were lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Pythium embraces 200 species. They are one of the most destructive plant pathogens, infecting crops and destroying the seeds, storage organs, roots, and other plant tissues [ 1 ]. The genus was considered as true fungi by Pringsheim in 1858 due to characteristics including eukaryotes with filamentous growth, absence of septa, nutrition by absorption, and reproduction via spores [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…They comprise living and dead microorganisms (e.g., bacteria), dispersal units (e.g., fungal spores, plant pollen), fragments (e.g., plant debris), and viruses (Després et al, 2012;Whon et al, 2012;Fröhlich-Nowoisky et al, 2016;Smets et al, 2016;Yahya et al, 2019;Pöhlker et al, 2021). Bioaerosols can serve as nuclei for cloud droplets and ice crystals influencing the formation of precipitation, and some of them are important allergens and pathogens (Brown and Hovmøller, 2002;D'Amato et al, 2007;Andreae and Rosenfeld, 2008;Steiner et al, 2015;Müller-Germann et al, 2017;Fröhlich-Nowoisky et al, 2016;Lang-Yona et al, 2018;Huang et al, 2021). The abundance and composition of bioaerosols are determined by local emission sources, meteorological conditions, and long-range transport (Jones and Harrison, 2004;Franzetti et al, 2011;Bowers et al, 2012Bowers et al, , 2013Gandolfi et al, 2013;Cao et al, 2014;Archer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%